Strategy for Exploring Children's Talent by Early Childhood Teacher: Method, Constraint, and Solution - Taufikin Taufikin; Sri Nurhayati; Maskanatul Fiqiyah (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
Early childhood talent exploration by Early Childhood Education (ECED) teachers is an essential challenge in optimizing children's future potential. However, teachers' methods are often insufficiently structured, with constraints regarding training, limited time, and resources. This study aims to explore the methods used by ECD teachers in researching children's talents and the constraints they face in implementing these strategies. The technique used was a qualitative approach with a case study involving in-depth interviews with 10 teachers and observations in three PAUD institutions. The results show that spontaneous observation, project-based activities, and standardized evaluation tools are the primary methods teachers implement. However, most teachers face constraints regarding lack of training, limited time, and inadequate resources. To improve the effectiveness of talent acquisition, this study suggests the importance of continuous training, increased resources, and the application of more systematic evaluation methods. The findings contribute to the development of early childhood education theory and practice and point to the need for policies that support the development of teachers' skills in identifying and developing children's talents.